Periodic assessment of (ET-1) and Nitric Oxide(NO) in hypertensive disorders of pregnancy (HDP) - Ismawi, Hidayatul Radziah; Abdul Razak, Tariq; Jamani, Nurjasmine Aida; Mohd Zainudin, Maizura (2019)
Hypertensive Disorders of Pregnancy (HDP) is an independent risk factors of cardiovascular (CVS) disease.